2014
DOI: 10.1007/s10546-014-9972-9
|View full text |Cite
|
Sign up to set email alerts
|

Near-Surface Motion in the Nocturnal, Stable Boundary Layer Observed with Fibre-Optic Distributed Temperature Sensing

Abstract: The evolution of cold air layers near the surface was investigated for a night with stable conditions near the surface. Spatial air temperature observations at 276 co-located vertical profiles were made using high-resolution fibre-optic based distributed temperature sensing (DTS) in a quasi three-dimensional geometry oriented along a shallow depression in the landscape and analysed for patterns in near-surface flow. Temperature stratification was observed to be interrupted by transient temperature structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 23 publications
1
56
0
Order By: Relevance
“…In DTS, a coherent pulse of light is sent down the cable, and continuous measurements of Raman backscattered light spectra allows for determination of the temperature at each point in the cable (Tyler et al ; Hausner et al ). DTS technology has been used in various environmental monitoring programs in the past, providing high spatial (< 1 m) resolution temperature measurements at scales of meters to kilometers (Selker et al ; Tyler et al ; Hausner et al ; Suárez et al ; Vercauteren et al ; Van Emmerik et al ; Kobs et al ; Zeeman et al ).…”
Section: Methodsmentioning
confidence: 99%
“…In DTS, a coherent pulse of light is sent down the cable, and continuous measurements of Raman backscattered light spectra allows for determination of the temperature at each point in the cable (Tyler et al ; Hausner et al ). DTS technology has been used in various environmental monitoring programs in the past, providing high spatial (< 1 m) resolution temperature measurements at scales of meters to kilometers (Selker et al ; Tyler et al ; Hausner et al ; Suárez et al ; Vercauteren et al ; Van Emmerik et al ; Kobs et al ; Zeeman et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Commercial instruments can obtain temperature continuously at resolution of 0.01°C, every meter, over distances of up to 10,000 m [Selker et al, 2006a]. It has also been useful in the atmospheric boundary to investigate turbulent structures [Sayde et al, 2015;Thomas et al, 2011;Zeeman et al, 2015]. It has also been useful in the atmospheric boundary to investigate turbulent structures [Sayde et al, 2015;Thomas et al, 2011;Zeeman et al, 2015].…”
Section: Experiments Setupmentioning
confidence: 99%
“…[] and Zeeman et al . [] have demonstrated that this technology can be used to observe air temperature and thermal structure of near‐surface turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of DTS to report temperature at such resolution has opened up many opportunities in environmental monitoring [e.g., Selker et al, 2006aSelker et al, , 2006bTyler et al, 2008Tyler et al, , 2009Steele-Dunne et al, 2010] including applications in the atmosphere [Keller et al, 2011;Petrides et al, 2011]. Recently, Thomas et al [2012] and Zeeman et al [2015] have demonstrated that this technology can be used to observe air temperature and thermal structure of near-surface turbulence. • Text S1 and S2, Figures S1-S4, Table S1, and Movie S1 Caption • Movie S1…”
Section: Introductionmentioning
confidence: 99%